Hubungan Antara Efikasi Diri dengan Intensi Berwirausaha pada Mahasiswa Fakultas Psikologi Universitas Muhammadiyah Surakarta - Karimah, Nirmala Ummi, Drs. Daliman, SU (2016)
Unemployment issue and high population growth each year into an issue that always faced in Indonesia. Therefore the role of entrepreneur is needed to solve it. There were issues about less job opportunities whereas college graduates increase, less confident individual to begin entrepreneur, so that more unemployment could happen. Hopefully the student can change their mindset that only oriented to be job seeker after past graduate from their college, but also has an intention and self efficacy strongly to be a success entrepreneurs, and able to create a new business for create job upportunities. The aims of research is to investigate correlation between self efficacy with entrepreneurship intention, effective contribution of self efficacy on entrepreneurship intention, the level of self efficacy and entrepreneurship intention. The research method of research used is quantitative approach with 100 respondents sixth grade and that takes entrepreneurship study with percentage absence at least 75%. The data were collected with self efficacy and entrepreneurship intention scale. Meanwhile, the sampling of method in this research used purposive sampling. Based on result with product moment, it was obtained the score of the coefficient of correlation (rxy) amount 0.846; significance (p) = 0.000 (p < 0.01), that means there were a positively significant correlation between self-efficacy and entrepreneurship intention. The effective contribution of the variable self efficacy on entrepreneurship intention of student amount 71,6% and left 28,4% obtained from another variables. It was founded in the research that self efficacy and entrepreneurship intention on student relatively high.